Comment: Measurement and the Interpretation of Trait EI Research. (October 2016) - Laborde, Sylvain; Allen, Mark S.
In this brief commentary, we present a critical reflection on trait emotional intelligence (EI) theory and research as covered in a recent narrative review (Petrides et al., 2016). We consider (a) whether synthesising research findings that use different conceptualisations of EI is desirable, (b) if the measurement of trait EI might become more diverse, (c) whether trait EI research in interpersonal settings requires additional analytical thought, and (d) how researchers might go about objectively conceptualising trait EI. Our collective focus is on EI measurement as it relates to the development of trait EI theory and research in the future.